Optimalisasi Masyarakat Desa Lubok Batee dalam Menghadapi Tanggap Darurat Pandemi Covid-19 - Risna Safitri; Muslem (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
This community service aims to provide education and socialization in understanding the dangers, prevention, transmission, and how to break the chain of the spread of covid-19. The method used in this community service is in education and socialization of a clean and healthy lifestyle to anticipate the spread of Covid-19 by distributing masks, making hand sanitizer s, washing clean and correct hands, and doing healthy exercise. The result of this community service activity is that residents gain knowledge through the education and socialization stages in distributing free masks, making hand sanitizer s, and washing their hands clean and properly. The implementation of education and outreach encourage residents of Lubok Batee Village practicing a clean and healthy lifestyle. They understand how to use masks, provide hand washing facilities, avoid direct contact with other residents, comply with health protocols, know the types of disposable masks and types of re-wash masks. Furthermore, they have better understanding the lifestyle patterns and behaviors in society by consuming healthy foods in a balanced manner.